Punishment Of Perpetrators Of Criminal Acts That Intentionally Place And Carry Out Economic And Sexual Exploitation Of Children Is Linked To The Principle Of Justice - Purba, Nelvitia -; Marlina, Marlina -; Batubara, Ismed - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Law is a social control instrument that may be used to decide or regulate people's conduct to ensure that it complies with the law. One of the crimes that is increasingly gaining attention worldwide is Commercial Sexual Exploitation of Children (CSEC), which is defined as the use of girls and/or boys for sexual activities that are paid for with cash or in kind items. Law enforcement and the government have made an effort to combat the crime of commercial sexual exploitation of minors by enforcing laws and implementing measures such as requiring judges to be courageous and experienced in executing the law in order to achieve justice. There are still many instances of child prostitution, which calls for a more thorough investigation.